Disease Burden of Chronic Kidney Disease Due to Hypertension From 1990 to 2019: A Global Analysis - Chen, Aiming; Zou, Minjie; Young, Charlotte Aimee; Zhu, Weiping; Chiu, Herng-Chia; Jin, Guangming; Tian, Lin (Frontiers in Medicine, 2021)
Background: Although it is widely known that hypertension is an important cause of chronic kidney disease (CKD), little detailed quantitative research exists on the burden of CKD due to hypertension. Objective: The objective of the study is to estimate the global disease burden of CKD due to hypertension and to evaluate the association between the socioeconomic factors and country-level disease burden of CKD due to hypertension. Methods: We extracted the disability-adjusted life-year (DALY) numbers, rates, and age-standardized rates of CKD due to hypertension from the Global Burden of Disease Study 2019 database to investigate the time trends of the burden of CKD due to hypertension from 1990 to 2019. Stepwise multiple linear regression analysis was performed to evaluate the correlations between the age-standardized DALY rate and socioeconomic factors and other related factors obtained from open databases. Results: Globally, from 1990 to 2019, DALY numbers caused by CKD due to hypertension increased by 125.2% [95% confidential interval (CI), 124.6 to 125.7%]. The DALY rate increased by 55.7% (55.3 to 56.0%) to 128.8 (110.9 to 149.2) per 100,000 population, while the age-standardized DALYs per 100,000 population increased by 10.9% (10.3 to 11.5%). In general, males and elderly people tended to have a higher disease burden. The distribution disparity in the burden of CKD due to hypertension varies greatly among countries. In the stepwise multiple linear regression model, inequality-adjusted human development index (IHDI) [β = −161.1 (95% CI −238.1 to −84.2), P < 0.001] and number of physicians per 10,000 people [β = −2.91 (95% CI −4.02 to −1.80), P < 0.001] were significantly negatively correlated with age-standardized DALY rate when adjusted for IHDI, health access and quality (HAQ), number of physicians per 10,000 people, and population with at least some secondary education. Conclusion: Improving the average achievements and equality of distribution in health, education, and income, as well as increasing the number of physicians per 10,000 people could help to reduce the burden of CKD due to hypertension. These findings may provide relevant information toward efforts to optimize health policies aimed at reducing the burden of CKD due to hypertension.